Real time object detection and tracking using the kalman filter embedded in single board in a robot - Guapacha, Jovanny Bedoya [UNESP]; Mantovanni, Suely Cunha Amaro [UNESP] (My University, 2017)
This paper presents an algorithm implemented in real time in a laboratory robot, designed to trace and detect the color of an object in an indoor environment using the kalman filter. The image capture is done by a kinect camera installed in the robot. The algorithm is programmed into a single board computer, BeagleBone Black that uses the ROS - OpenCV system in image processing.
Keywords: Kalman filter; Kinect; Single board computer; Tracking; Visual computation